Overcoming informal barriers to trade: Immigrant educational attainment vs. network competence. Issue 1 (February 2022) - Yang, Xiyan; Lin, Xiaohua
Highlights: Only immigrants with a low level of education facilitate south→north trade. Only highly educated immigrants facilitate north→north trade. Advantage derives from differential endowments of social vs. human capital. Network competence helps overcome institutional void in south→north trade. Educational attainment helps overcome informational void in north→north trade. Abstract: Focusing on developed countries as the destination of both migrants and traded goods, we adopt a contingent perspective to examine the efficacy of immigrant resources in the promotion of international trade. We find that only immigrants with a low level of education facilitate trade when they originate from a developing source country (south→north trade), whereas only highly educated immigrants facilitate trade when they originate from a developed source country (north→north trade). This difference emerges from the immigrant's role in helping overcome two distinct informal barriers to trade based on their different resource endowments in terms of network competence vs. educational attainment.